THU0274 Footprints of neutrophil extracellular traps are elevated in patients with systemic lupus erythematosus. (15th June 2017) - Jeremic, I; Djuric, O; Nikolic, B Bonaci
Abstract : Background: Impaired removal of apoptotic waste in patients with systemic lupus erythematosus-SLE has been long known as important factor that trigger autoimmune response. Neutrophil extracellular traps could be another source of autoantigens in patients with SLE. Objectives: The aim of this study was to compare NETs markers (free DNA, myeloperoxidase) and dnase I in SEL patients and healthy controls, as well to assess their relationship with serological markers of SLE disease activity (C3 and C4 complement components, anti-dsDNA antibodies) and SLEDAI score (clinical disease activity index). Methods: We analysed 111 sera obtained from 84 SEL patients (60 patients had 1 sample and 24 patients had 2 or 3 samples) and 50 healthy blood donors. Serum levels of myeloperoxidase, B-cell activating factor-BAFF, cell free DNA, complement components C3 and C3, antibody to dsDNA by CLIFT end ELISA assays, netolitic activity and DNAse I were measured. The group of 35 patients was selected (11 with de novo disease) for which clinical data were recorded. Results: SLE patients had significantly higher concentration of free serum DNA (1.69±0.23 vs. 1.42±031 ng/mL, p=0.0003), dnase I (10.4±6.9 vs. 5.8±5.7 U/mL, p<0.05), anti-MPO antibodies (13.8±43.4 vs. 0.9±0.3 U/mL, p<0.001) and myeloperoxidase activity (1607±2353 vs. 560.3±182.5 RU, p<0.05) in comparison to healthy controls. The ability of sera to degrade NETs was similar in both groups. Free DNA, dnase I, BAFF and anti-MPO levels as well myeloperoxidase activity showed significant correlation with anti-dsDNA antibodies measured by ELISA test. None of studied parameters showed correlation with C3 and C4 complement components. C3 and anti-dsDNA antibodies measured by indirect immune fluorescence were independent predictors of SLEDAI score in multivariate analysis, while BAFF and dnase I were significant in univariate analysis. Free cDNA was predictor of SLEDAI score higher than 7 in univariate analysis. Conclusions: Increased amount of NETs markers found in lupus sera confirms their role in SLE pathogenesis. Determination of NETs markers could be useful serological parameter to follow disease activity in SLE patients. References: Skiljevic D, Jeremic I, Nikolic M, Andrejevic S, Sefik-Bukilica M, Stojimirovic B, et al. Serum DNase I activity in systemic lupus erythematosus: correlation with immunoserological markers, the disease activity and organ involvement. Clin Chem Lab Med. 2013;51(5):1083–91. Garcia-Romo GS, Caielli S, Vega B, Connolly J, Allantaz F, Xu Z, et al. Netting Neutrophils Are Major Inducers of Type I IFN Production in Pediatric Systemic Lupus Erythematosus. Sci Transl Med.2011;3(73):7. Hakkim A, Fürnrohr BG, Amann K, Laube B, Abed UA, Brinkmann V, et al. Impairment of neutrophil extracellular trap degradation is associated with lupus nephritis. Proc Natl Acad Sci U S A. 2010;107(21):9813–8. Disclosure of Interest: None declared